Deutsche Wirtschaft gut ausgelastet – Wirtschaftspolitik neu ausrichten - Roland Döhrn; Ferdinand Fichtner; Oliver Holtemöller; Stefan Kooths; Timo Wollmershäuser (Wirtschaftsdienst, 2016)
Die deutsche Wirtschaft befindet sich in einem moderaten Aufschwung. Die Gemeinschaftsdiagnose Herbst 2016 prognostiziert, dass das Bruttoinlandsprodukt 2016 um 1,9%, 2017 um 1,4% und 2018 um 1,6% zulegen dürfte. Dabei gehen von der Weltkonjunktur nur geringe stimulierende Effekte aus, zudem dürften sich in den außerordentlich niedrigen Kapitalmarktzinsen nicht nur die derzeitige Geldpolitik, sondern auch niedrige Wachstumserwartungen widerspiegeln. All dies hemmt die Ausrüstungsinvestitionen. So ist es weiterhin in erster Linie der Konsum, der den Aufschwung trägt. – – The German economy is experiencing a moderate recovery: GDP is expected to grow by 1.9 percent this year, 1.4 percent next year, and 1.6 percent in 2018. Over the course of the forecast period, capacity utilisation will be somewhat higher than in the longterm average. Nevertheless, the contribution of corporate investment to the current upswing is minimal. The global economy is generating only minor stimulating effects, which means that exports are increasing only moderately. The extremely low long-term interest rates are likely to refl ect not only the current monetary policy, but also low growth expectations. All of these factors are inhibiting investment into equipment, and thus, consumption continues to be the main growth driver. Private consumption is benefiting from the sustained increase in employment; the high expenditures for accommodating and integrating the refugees is still having a strong impact on public spending. Residential construction is getting a boost from the low interest rates.
Keywords: E32; E66; F01; 330